ALGEBRA TEACHING METHODOLOGY - Masimova Gulmira Maxsutovna; Raxmatova Gulrux Axatovna (American Journals Publishing, 2024)
This article is about methods, methods of teaching mathematics how important mathematics is to students, the importance of science is shown in student teran thinking.
Keywords: Math, life, space, oily, science, teacher, student, elementary mathematics.